Analise espacial da taxa de homicidios nos municípios do estado de Alagoas no ano de 2010 - Silva, Rhafaella Karlla Costa Santana da (2019)
This paper aims to test the hypothesis of spatial dependence of crime rate in the municipalities of Alagoas and to verify possible determining factors for the year 2010. Crime in society is a complex problem, which exhibits a large number of interpretations and has now become. incorporate a research agenda in economics mainly after the work of Gary S. Becker (1968). In a more recent scenario, note a growing interest between the sociodemographic and geographical aspects of crime. In 2010, the state of Alagoas led the Brazilian ranking of the crime rate. Both homicide data and dependent variables come from the Ministry of Health's DATASUS. Other dependent variables from the IBGE Census (2010). An Exploratory Spatial Data Analysis was performed to describe and visualize spatial distributions through Moran Global and Local (LISA) statistics. Through the application of the Space Lag model, the levels of increase or crime rate that were accompanied by important transformations were applied to youth, income concentration and economic activity.